SAT0337 Biologic dmards and psoriatic arthritis in europe in 2016/2017: characteristics of patients starting tnf-inhibitors or ustekinumab in the ongoing psabio observational cohort study. (12th June 2018) - Gossec, L.; Athanassiou, P.; Bergmans, P.; de Vlam, K.; Gremese, E.; Joven-Ibáñez, B.; Korotaeva, T.V.; Lioté, F.; Nurmohamed, M.T.; Sfikakis, P.P.; Siebert, S.; Smirnov, P.; et al.
Abstract : Background: The PsABio study (ClinicalTrials.gov Id: NCT02627768 ) was developed to evaluate the efficacy, tolerability and persistence of TNF inhibitors (TNFi) and ustekinumab (UST) for patients with psoriatic arthritis (PsA) starting 1 st, 2nd or 3rd line biologic disease-modifying antirheumatic drugs (bDMARDs) in real-world routine care. Objectives: In this interim analysis, the objective was to describe the profile of patients starting either UST or TNFi in routine clinical care in 8 European countries. Methods: Between Dec 2015 and, Aug 2017 patients were enrolled in Italy, Greece, Russia, France, United Kingdom, The Netherlands, Spain and Belgium and had valid baseline data available. Descriptive baseline characteristics for the UST and TNFi cohorts were compared. Results: 563 consecutive patients were analysed (278 UST- and 285 TNFi-treated patients): mean (SD) age 49.3 (12.4) years, disease duration 7.2 (7.5) years; 49.6% were men and most had polyarticular disease (Table). Among comorbidities, cardiovascular disease (38.9%) and obesity (30.4%) were most frequent; 11.5% had anxiety or depression. 25.6% of patients were current smokers. TNFis were more often given as 1 st line bDMARD than UST (56.8% vs 39.2%). For patients receiving their 1 st bDMARD, the prevalence of concomitant conventional synthetic (cs) DMARDs at baseline was: UST: 46.8% (39.5% methotrexate [MTX]) and TNFi: 53.7% (39.5% MTX). Among 166 patients who received a 2nd or 3rd bDMARD and had no ongoing csDMARDs at baseline, 66.3% received UST and 33.7% received TNFi. The most prescribed TNFi were etanercept (34.0%), adalimumab (25.3%) and golimumab (19.6%); 12.6% were TNFi biosimilars. The majority of patients on UST received the recommended dose, although 27.8% (10/36) of patients>100 kg started with 45 mg every 3 months. Disease activity was moderate to high with more axial, skin and nail involvement in the UST group. Conclusions: European PsA patients starting bDMARDs in 2016/2017 frequently presented with moderate to high disease activity, and overlapping subtypes of PsA, mainly polyarticular disease. Comorbidities, predominantly cardiovascular, were common. Compared to patients treated with TNFi, UST was more often given as 2nd or 3rd line bDMARD and in patients with more axial and skin disease. Among patients who switched to a 2nd or 3rd line bDMARD, those not on concomitant csDMARDs preferentially received UST. Acknowledgements: This study was sponsored by Janssen. Disclosure of Interest: L. Gossec Grant/research support from: Pfizer, Consultant for: AbbVie, Celgene, Janssen, Lilly, Novartis-Sandoz, Pfizer, Sanofi, and UCB, P. Athanassiou: None declared, P. Bergmans Shareholder of: Johnson and Johnson, Employee of: Janssen, K. de Vlam Consultant for: Johnson and Johnson, E. Gremese Consultant for: AbbVie, Janssen, Lilly, Pfizer, Speakers bureau: AbbVie, Janssen, Lilly, Pfizer, B. Joven-Ibáñez Speakers bureau: Celgene, Novartis, MSD, Pfizer, AbbVie, and Janssen, T. Korotaeva Consultant for: Pfizer, MSD, Novartis, AbbVie, Celgene, Biocad, Janssen, and UCB, Speakers bureau: Pfizer, MSD, Novartis, AbbVie, Celgene, Biocad, Janssen, and UCB, F. Lioté Grant/research support from: Principal investigator or Co-PI for Janssen, MSD, Pfizer, Novartis, AbbVie, and Celgene, Consultant for: Advisory boards for Celgene and MSD, M. Nurmohamed Grant/research support from: Received research support to his institution from Pfizer, AbbVie, Roche, BMS, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, and Celgene, Consultant for: Pfizer, AbbVie, Roche, BMS, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, and Celgene, Speakers bureau: Pfizer, AbbVie, Roche, BMS, MSD, Mundipharma, UCB, Janssen, Menarini, Eli Lilly, Sanofi, and Celgene, P. Sfikakis: None declared, S. Siebert Grant/research support from: Receipt of grants/research support to his institution from Pfizer, Janssen, BMS, Celgene, UCB, and Boehringer Ingelheim. participation in clinical trials with AbbVie, Novartis, and UCB, Consultant for: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, Speakers bureau: AbbVie, UCB, Pfizer, Janssen, Boehringer Ingelheim, Celgene, and Novartis, P. Smirnov Employee of: Janssen, E. Theander Employee of: Janssen, J. Smolen Grant/research support from: Received grants for his institution from AbbVie, Janssen, Lilly, MSD, Pfizer, and Roche, Speakers bureau: Provided expert advice to and/or had speaking engagements with AbbVie, Amgen, Astra-Zeneca, Astro, Celgene, Celtrion, GlaxoSmithKline, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, and UCB